Indicators of Natural Resource Conflict in Farmer Communitiesin Kendeng Mountains, Central Java - Hadi Suyono; Suryanto Suryanto (Universitas Ahmad Dahlan, 2018)
The aim of the study is to determine the indicators of natural resource conflicts in the farming communities in Kendeng Mountains who chose to focus on the reality of natural resource conflicts. This study uses a qualitative method with a phenomenological approach to uncover social experiences and gain meaning.Subjects were selected based on purposive sampling technique, respondents were determined according to the characteristics that had been previously chosen. Respondents were farmers who owned land in Kendeng Mountains region in Pati and Rembang Regency, Central Java. Respondents were farmers affected by mining natural resources in the form of karst. Furthermore, data is obtained using semi-structured interview techniques and analyzed using steps to proceed, prepare, and read data, do coding, write down settings, describe respondents, create categories, describe themes, present in narrative form, and interpret.Our findings show that indicators of natural resource conflict in the farming community in Kendeng Mountains are lifeÂ threat, leader distrust, motivation, social capital, and social identity. A more detailed description of this research can be seen in the section below.Keywords: Indicators of conflict, natural resources, farming communities